Reduced levels of ALS gene DCTN1 induce motor defects in Drosophila - Borg, Rebecca; Herrera, Paul; Purkiss, Angie; Cacciottolo, Rebecca; Cauchi, Ruben J. (Frontiers in Neuroscience, 2023)
Amyotrophic lateral sclerosis (ALS) is a rapidly progressive neuromuscular disease that has a strong genetic component. Deleterious variants in the DCTN1 gene are known to be a cause of ALS in diverse populations. DCTN1 encodes the p150 subunit of the molecular motor dynactin which is a key player in the bidirectional transport of cargos within cells. Whether DCTN1 mutations lead to the disease through either a gain or loss of function mechanism remains unresolved. Moreover, the contribution of non-neuronal cell types, especially muscle tissue, to ALS phenotypes in DCTN1 carriers is unknown. Here we show that gene silencing of Dctn1, the Drosophila main orthologue of DCTN1, either in neurons or muscles is sufficient to cause climbing and flight defects in adult flies. We also identify Dred, a protein with high homology to Drosophila Dctn1 and human DCTN1, that on loss of function also leads to motoric impairments. A global reduction of Dctn1 induced a significant reduction in the mobility of larvae and neuromuscular junction (NMJ) deficits prior to death at the pupal stage. RNA-seq and transcriptome profiling revealed splicing alterations in genes required for synapse organisation and function, which may explain the observed motor dysfunction and synaptic defects downstream of Dctn1 ablation. Our findings support the possibility that loss of DCTN1 function can lead to ALS and underscore an important requirement for DCTN1 in muscle in addition to neurons.